Teaching Speaking Through Debate Technique - . Suranto (Jurnal Pendidikan Edutama, 2016)
Abstract : Teaching Speaking Through Debate Technique. Speaking is one of the basic competence from the other fourth basic competence (listening, speaking, reading and writing). Speaking ability should be mastered by every students, in order to achieve that competence students should be given the right technique to study sepaking. The successfull of the students speaking can be seen from their ability to express idea, thought and feeling through speaking. The objective of this Action Research is to improve students’s oral communication skill through the debate technique. This study was conducted at MA Ma’arif Nu 5 Sekampung Lampung Timur from March to April 2014. The research data were taken from students in the eleventh class, with 28 students and analyzed qualitatively and quantitatively. The research findings indicate that there are improvements in students’ english speaking skill through the debate technique. By analyzing data qualitatively and quantitatively from the end of the first cycle to the second cycle and it was found that the students’ English speaking skill increased 20,9% over the standard that has been determined by the researcher that is 65%. The researcher concludes that the students’ english speaking skill can be improve through the debate technique in learning process.  Key words : action research, debate technique, english speaking skill